Desenvolvimento e avaliação de uma vacina inativada contra estirpe variante brasileira do vírus da bronquite infecciosa aviária - Santos, Romeu Moreira dos [UNESP] (2014)
The infectious bronchitis (BIG) is an infectious disease caused by avian coronavirus (infectious bronchitis virus - IBV) that is widespread among commercial poultry flocks in the world. There are currently in Brazil, a predominance of infections caused by strains of IBV classified in variant genotype (BR-I), which reveal striking differences in antigenicity with regard to the vaccine strain Massachusetts, routinely used in this country. The consequence is a low cross-immunity and lower level of protection against Brazilian field isolates of genotype BR-I. Thus, the main objectives of this study were to formulate an experimental inactivated vaccine with a variant strain of IBV previously characterized as genotype BR-I and added of a new oil adjuvant and test it after an administration, at 1 day old, of a commercial attenuated Massachusetts vaccine, followed by the evaluation of humoral and cellular immune (CMI) responses, as well as the state of protection upon challenge with this variant strain of IBV by histopathological examination and absolute quantification of viral load present in the trachea, and kidneys of these birds vaccinated and challenged with this variant strain. The results of this study demonstrated that this immunoprophylactic approach (vaccination of birds with 1 day old with attenuated commercial vaccine and revaccination at 14 days of age with annual experimental inactivated vaccine) was able to elicit significant increases in the serum and tear levels of anti-IBV antibodies of IgG isotype, and also in the expression of CMI genes, especially of CD8  chain and Granzyme A in the vaccinated birds, which were associated with decreased histological lesions and reduced viral load in the trachea and kidney of vaccinated and challenged birds. It was concluded that humoral and cellular memory immune responses conferred by vaccination with this Brazilian variant strain of IBV combined to a previous Massachusets ...